Tantangan dan Peluang dalam Meningkatkan Kompetensi Profesional Guru Pendidikan Agama Kristen di Era Digital - Sipahutar, Friska Mawarni; Naibaho, Dorlan (Jurnal Pendidikan Non formal, 2023)
Professional competence in the context of Christian religious education refers to in-depth abilities in mastering subject matter and fields of study. Professional Christian Religious Education teachers are expected to be able to master academic study materials, apply PAK material in depth, and develop themselves through updating science and technology information to find the right technology to use in PAK learning. The purpose of this paper is to evaluate the challenges and opportunities faced by teachers in achieving professional competence in developing technology into Christian religious education in the digital era. The research method used is a qualitative approach based on analysis on literature and data from accredited academic articles. Thus it can be concluded that incorporating technology into the Christian religious learning environment can open up great opportunities to improve students' learning experiences and expand the reach of Christian religious education materials. However, teaching professionals need to meet these challenges with appropriate policies and strategies to ensure that the use of this technology supports the strong and essential goals of Christian religious education.